Is the Euro Area an Economic mistake? The OCA Theory Approach. - Drobík, Michal; Petrášek, František, 1934-; Mládek, Josef; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2012)
The diploma thesis is aimed to apply the theoretical concept of optimum currency areas, i.e. probably the most comprehensive approach to analyze the suitability of establishing a currency area, to the real and currently difficulties solving environment of EMU states. The first, theoretical-methodological part shows the development of the OCA theory, as founded by Robert A. Mundell and expanded upon by further contributors and critics thereafter. This part focuses especially on defining the optimality criteria, which are then analyzed in the empirical-analytical section. In order to assess the level of optimality, which the euro area members have reached during the common currency existence period, concrete and empirical data are analyzed - data, showing the previous development of the selected indicators, describing the criteria fulfilling. In the final part of the thesis, the author considers the overall optimality rate of euro area and points out its consequences for the Czech Republic, as a candidate country. Furthermore, the entry-timing question is discussed as well, when finished by a two possible scenarios of our accession to EMU. In relation to this issue, the author also discusses the relevancy to assess the readiness for entering the euro area according to the parameters of Maastricht criteria.
Vedoucí práce: František Petrášek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses